Large critical current densities in a silver-sheathed (Sr, Na)Fe2As2 tape. (28th August 2015) - Iyo, A; Shinohara, N; Tokiwa, K; Ishida, S; Tsuchiya, Y; Ishii, A; Asou, T; Nishio, T; Matsuzaki, K; Takeshita, N; Eisaki, H; Yoshida, Y
Abstract: We report the first superconducting tape using an iron-based superconductor (Sr, Na)Fe2 As2 fabricated by the powder-in-tube (PIT) technique. Polycrystalline (Sr1− x Na x )Fe2 As2 ( x  = 0.55), which we recently succeeded in synthesizing, was used as the starting powder. First, a silver (Ag) tube was groove-rolled into a square wire. The wire was then flat-rolled into tape form, followed by uniaxial cold pressing. The heat-treated tape exhibits a sharp superconducting transition at 34.5 K. Large transport critical current densities ( J c ) of over 1.0 × 10 4 A cm −2 are achieved at 20 K under a magnetic field of 2.5 T. J c at 4.2 K, as estimated from magnetic hysteresis curves, is 1.0 × 10 5 A cm −2 in 2.0 T, which is comparable to the transport J c reported for ( AE, K)Fe2 As2 ( AE  = Ba or Sr) tapes. SEM-EDX observations indicate that some Ag and As-rich material is present between (Sr, Na)Fe2 As2 grains, even though no Ag was added to the starting powder. This Ag and As-rich material may strengthen grain connectivity and help to improve the transport J c .